(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
In a state of existential fear of a possible Soviet military invasion after the Cominform resolution of 1948, the Yugoslav regime began persecuting the political opposition, organizing “Kafkaesque” trials, imprisonments and exiles, sending thousands of people to forced labor in so-called re-education camps. This highly paradoxical “Yugoslav Gulag”, became the main vehicle for this systemic and systematic political violence, which continued with varying degrees of intensity until 1956. At the end of the 1980s and the beginning of the 1990s, in other words only after Tito’s death and the subsequent drastic weakening of party censorship, a series of texts began to emerge which, despite their formal and generic heterogeneity, is united by a common thematic framework: the Goli otok camp. For the former prisoners, the only way to reclaim their own confiscated experience was to write about it. The aim of our work is to put the unpublished memoires from Goli Otok written by Đina Markuš in a perspective with the already known testimonies of women from Tito’s labor camps and include them among the texts of Milka Žicina, Ženi Lebl, Rosa Dragović-Gašpar, Vera Cenić, Eva Grlić and others. Particular attention is paid to what we identify as the key elements of the poetics of Markuš’s memoirs: the question of articulating memory and oblivion, writing as a way of dealing with trauma, and the relationship between text-museum and body-archive as a female camp paradigm. The aim of our article is to use the example of Đina Markuš’s memoires in order to understand the literature written by women detained in the Yugoslav camps as a poetic manifestation of the de-confiscation of their own history – a question that is both aesthetic and political